EFFECTS OF FEEDING COLOSTRUM AND MILK OF HOLSTEIN COWS ON GROWTH RATE, IMMUNOGLOBULIN LEVELS AND METABOLIC TRAITS IN JERSEY CALVES PRODUCED BY EMBRYO TRANSFER: COMPARISON WITH HOLSTEIN CALVES - D. H. Lim; V. U. Mayakrishnan; K. S. Ki; Tae Il Kim1 (Journal of Animal and Plant Sciences, 2017)
The aim of the present study wasto assess the effects of Holstein dam’s colostrum and milk on growth rate, immunoglobulin levels, and metabolic traits in Jersey calves produced by embryo transfer: comparison with Holstein calves. All calves received colostrum within half an hour after birth at the rate of 2.4-3.9 Lwere 10% BW basis, and continued for the first 3 days and milk from after that to weaning at 8 weeks; they were fed twice daily in equal amounts more or less5-10% of their BW. Also, calves were provided water ad libitum, grass hay, and calf starter at 7 days after birth. Results exhibited the content and immunoglobulin levels of colostrum gradually decreased with increasing age after birth. Jersey calves had lower BW (P<0.05)at preweaning period and mean ADG over 56 days compared with Holstein calves (P>0.05). However, feed efficiency was higher in Jersey than in Holstein calves (P>0.05). The level of plasma IgG was over 10 mg/mL, which indicated the successful transfer of passive immunity in Jersey and Holstein calves. Indeed, feeding the milk of Holstein dams did not significantly affect plasma total protein, glucose, urea nitrogen, and NEFA concentrations of Jersey calves as compared with Holstein calves. Therefore, these data suggest that feeding Holstein dam’s milk will not affectthe growth performance, immunoglobulin level and metabolic traits of Jersey calves produced by embryo transfer.
Keywords: Embryo transfer; Holstein dam’s milk; Growth rate; Immunoglobulin; Metabolic traits